Building an Attractive Purchasing Experience: The Vital Role of Store Atmosphere and Word of Mouth in Fiksi Coffee, Majalengka Regency - Pipih Sopiyan; Masduki; Indri Mayangsari (Finance and Business Management Journal, 2024)
A promising long-term business opportunity can be realized by opening a café with attractive features to captivate consumer attention and curiosity. Amidst the proliferation of cafés, consumers have the freedom to choose a comfortable café, with the primary goal for business owners being consumer purchase decisions. This study aims to explore the impact of store atmosphere and word of mouth on purchase decisions at Fiksi Coffee in Majalengka Regency. A quantitative approach is employed, with descriptive and verificative methods. The study population comprises consumers of Fiksi Coffee in Majalengka Regency, with a sample of 96 respondents selected using incidental sampling techniques. Data were collected through questionnaires using a Likert scale as the measurement tool. Data analysis was conducted using multiple linear regression and coefficient of determination, preceded by classical assumption tests and followed by hypothesis testing. The results indicate that both store atmosphere and word of mouth have a positive and significant partial impact on purchase decisions at Fiksi Coffee. This suggests that the better the store atmosphere and word of mouth provided, the higher the purchase decision rate at Fiksi Coffee in Majalengka.